Companionship during Childbirth: Pregnant Women’s Perception, Acceptability, and Preferences in a Tertiary Health Center in Northwestern Nigeria - Jamila Abubakar Garba; Zainab Kontagora Abdullahi; Saratu Bello; Abubakar Abubakar Panti; Amina Gambo Umar; Karima Abubakar Tunau (Archives of Medicine and Health Sciences)
Background and Aim: Companionship during childbirth has been identified as one of the indicators of quality of care during labor. Women who received companionship throughout labor have been found to have better outcome. The aim of this study was to determine the pregnant women’s perception, acceptability, and preferences for companionship during childbirth. Materials and Methods: This was a cross-sectional study among pregnant women attending antenatal care at a tertiary health center in Northwestern Nigeria. The data were obtained using an interviewer-administered questionnaire. Analysis was done using SPSS version 25. Results: Three hundred and forty-three respondents were recruited into the study. Among them, 193 (56.3%) were aware that they could have a companion during childbirth and 62 (18.1%) had a previous companion. Mothers were the companions for 19 (30.6%) and husbands were the companions for 16 (25.8%). The majority of the respondents (n = 243; 70.8%) believed that it is essential to have a companion during childbirth and 68.2% would accept having a companion during childbirth. The factors that were associated with the acceptability of having a companion during childbirth were educational status (P = 0.003) and awareness of companionship during childbirth (P < 0.001). Conclusion: The majority of the respondents believed that it is essential to have a companion during childbirth and are willing to accept it. The factors associated with the acceptability of having a companion during childbirth were educational status and awareness of companionship during childbirth.